Recruiting intensity - R. Jason Faberman (IZA World of Labor, 2020)
When hiring new workers, employers use a wide variety of different recruiting methods in addition to posting a vacancy announcement, such as adjusting education, experience, or technical requirements, or offering higher wages. The intensity with which employers make use of these alternative methods can vary widely depending on a firm's performance and with the business cycle. In fact, persistently low recruiting intensity partly helps to explain the sluggish pace of job growth in the US economy following the Great Recession, and the historically subpar wage growth during the subsequent expansion.
Keywords: E24; J60; 330; hiring; vacancies; recruiting; business cycle; unemployment